Buddy bites the bullet - Bagge, Peter 1957- (Fantagraphics, 2001)
The finale of the author's decade-long comic-book Bildungsroman. Includes the never-before-collected Stinky solo adventure, "King of the airwaves."
"The material in this collection originally appeared in Hate #22, 26-30"--Title page verso
Keywords: Bradley, Buddy (Fictitious character) / Comic books, strips, etc; Bradley, Buddy (Fictitious character); Comics (Graphic works); Graphic novels; Alternative comics; New wave comics; Comic books, strips, etc; Comic